Redescription and reevaluation of the generic status of Leptodactylus dantasi (Amphibia, Anura, Leptodactylidae) and description of its unusual advertisement call - De Souza, Moisés B. [UNESP]; Haddad, Célio F. B. [UNESP] (Society for the Study of Amphibians and Reptiles, 2003)
Leptodactylus dantasi Bokermann is redescribed from adult specimens collected in Parque Nacional da Serra do Divisor, State of Acre, Brazil, near the border between the Brazilian state of Acre and Peru. We propose the inclusion of this species in the genus Hydrolaetare. A new diagnostic character observed for the genus is the presence of fringes of fingers, and fringes and webbing of toes, finely serrate; the serrate edge of the fringe and webbing can be keratinized in males, females, and subadults. Hydrolaetare dantasi (Bokermann) is characterized by robust body and limbs, a broad and depressed head, slightly shorter than wide, and long, pointed and basally webbed toes. Hydrolaetare dantasi differs from the only other species in this genus, Hydrolaetare schmidti (Cochran and Goin), mainly by having toes webbed basally (fully webbed in H. schmidti). The advertisement call of H. dantasi is composed of two components; an initial note produced by the impact of the vocal sac against the ground and a second note corresponding to a long whistle of ascending frequency. The initial note is a percussive sound and represents an unusual form of sound emission in anurans; the second note is a vocalization.
Keywords: Amphibia; Anura; Hydrolaetare schmidti; Leptodactylidae; Leptodactylus; Leptodactylus dantasi